2007
DOI: 10.1016/j.appdev.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Dual language and literacy development of Spanish-speaking preschool children

Abstract: This article describes oral language and early literacy skills in Spanish and English for a sample of 319 bilingual children in Massachusetts and Maryland (ECS) and a comparison group of 144 monolingual Spanish-speaking children in Puerto Rico (PRC). Children were assessed as they entered and exited pre-kindergarten programs. Data collection included four subtests of the Woodcock Language Proficiency Battery and a researcher-developed phonological awareness task. Results show that, on average, children in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
134
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(152 citation statements)
references
References 19 publications
12
134
2
1
Order By: Relevance
“…However, the magnitude of these differences, between onethird and one-half of a standard deviation, were much smaller than we would expect in a comparison between L2 learners in their typical educational conditions and national monolingual norms, based on previous studies. For instance, three recent studies conducted with upper-elementary school students Kieffer & Lesaux, 2008;Proctor et al, 2005) found that L2 learners were more than one standard deviation below national norms for monolinguals on standardized English oral vocabulary measures, estimates that are consistent with those for L2 learners in the primary grades (e.g., Manis et al, 2004;Páez et al, 2007;Swanson et al, 2006). Our finding of relatively smaller differences suggests that L1 students and L2 learners from the same neighborhood, attending the same urban schools, and with similar educational histories are likely to be much closer in vocabulary knowledge than we would assume based on national comparisons of the two populations, in part because the vocabulary knowledge of L1 learners in these schools is also under-developed relative to age-based expectations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the magnitude of these differences, between onethird and one-half of a standard deviation, were much smaller than we would expect in a comparison between L2 learners in their typical educational conditions and national monolingual norms, based on previous studies. For instance, three recent studies conducted with upper-elementary school students Kieffer & Lesaux, 2008;Proctor et al, 2005) found that L2 learners were more than one standard deviation below national norms for monolinguals on standardized English oral vocabulary measures, estimates that are consistent with those for L2 learners in the primary grades (e.g., Manis et al, 2004;Páez et al, 2007;Swanson et al, 2006). Our finding of relatively smaller differences suggests that L1 students and L2 learners from the same neighborhood, attending the same urban schools, and with similar educational histories are likely to be much closer in vocabulary knowledge than we would assume based on national comparisons of the two populations, in part because the vocabulary knowledge of L1 learners in these schools is also under-developed relative to age-based expectations.…”
Section: Discussionmentioning
confidence: 85%
“…Historically underserved and concentrated in underresourced schools, language minority students in the U.S. disproportionately demonstrate difficulties with reading comprehension (Kieffer, 2008(Kieffer, , 2010National Center for Educational Statistics, 2009). A growing research base supports the notion that L2 learners of English typically demonstrate below-average levels of English vocabulary knowledge (e.g., Garcia, 1991;Manis, Lindsey, & Bailey, 2004;Páez, Tabors, & López, 2007;Proctor, Carlo, August, & Snow, 2005;Swanson, Sáez, & Gerber, 2006). However, the majority of these studies have utilized a single measure of vocabulary breadth, raising questions about how differences between L1 and L2 learners' vary across different aspects of English vocabulary knowledge.…”
Section: Vocabulary Knowledge In First and Second Language Learnersmentioning
confidence: 96%
“…As stated previously, this issue has the potential to result in over-or underestimation of skills. Studies show that bilingual children's mean vocabulary scores on standardized assessments tend to be below those of monolingual children in both languages when each language (i.e., Spanish and English) is measured separately (Bialystok, Luk, Peets, & Yang, 2010;Hammer, Lawrence, & Miccio, 2008;Jackson, Schatschneider, & Leacox, 2014;Páez, Tabors, & López, 2007;Uccelli & Páez, 2007;Uchikoshi, 2006). Consequently, alternative measures have been proposed that take into account both languages of the bilingual child when appraising the lexicon.…”
Section: Bilingual Vocabulary Appraisalmentioning
confidence: 95%
“…Children with impoverished exposure to novel words and rich vocabulary-building curricula show language deficits [14,24]. Differences in vocabulary skills in preschool and kindergarten can predict differences in reading ability and language comprehension in middle and high school [17,28].…”
Section: Introductionmentioning
confidence: 99%